Pola Interaksi Antarbudaya Suku Jawa dan Batak Simalungun dalam Tradisi Rewang di Emplasmen Bah Butong Kabupaten Simalungun - Arum Sari Annar; Leylia Khairani (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2022)
This study focuses on intercultural interactions in the Rewang Tradition which is a tradition belonging to the Javanese Ethnic. The aim of this research is; (1) to find out what actions were taken while carrying out the Rewang tradition (2) to find out the response of the Simalungun Bataknese ethnic group to their interactions in the tradition. This study used a descriptive qualitative method. The data sources in this study were observations and interviews. The data obtained were obtained from 6 informants, namely 3 ethnic Javanese and 3 ethnic Simalungun Bataknese. Data analysis in this study using a qualitative descriptive method begins by examining all available data from various sources, namely interviews with informants and observations that have been written down in field notes. The stages in the data analysis process are data reduction, data presentation and conclusions or levers. The results obtained from this research are the actions taken in each series of events including pre rewang, namely holding counseling, asking for permission and asking for help regarding the event to be carried out (tonggo rojo). When rewang everyone involved does the task that has been mutually agreed upon. After rewang, the manufacture of marrow porridge is intended for people who are involved in rewang. inter-ethnic reciprocity regarding their involvement in every tradition they carry out is the hope of the Simalungun Bataknese and Javanese Ethnics.